A Teaching Method According to Hadith: Metode Mengajar Menurut Hadis - Lica, Arda Mei; Gayomi, Natasya; Rahma Salsabila; Khadijah, Saidah (Program Studi Pendidikan Agama Islam Universitas Muhammadiyah Kendari, 2025)
This paper explores the teaching methods demonstrated by Rasulullah ﷺ based on authentic hadiths, and their applicability in today’s educational context. The study eploys a qualitative descriptive approach through literature analysis. The findings indicate that Rasulullah ﷺ utilized various instructional techniques such as questioning, hands-on, practice, visual analogies, educational humor, exemplary conduct, and the reward and punishment. Each approach plays a crucial role in fostering student engagement, comprehension, and character formation. The alignment of these prophetic methods with current educational challenges shows their effectiveness in establishing interactive, meaningful, and ethically grounded learning environtmens. This study contributes to educational discourse by bridging traditional prophetic pedagogy with contemporary teaching approaches, emphasizing not only knowledge acquisition but also moral development. It is intended to serve as a guide for educators in creating spiritually enriching and pedagogically sound learning strategies. .